Effect of Deficiencies in the Tunnel Crown Thickness on Pressure Tunnels with Posttensioned Concrete Linings - Gan Qin; Shengrong Cao; Fan Yang (Advances in Civil Engineering)
This paper investigates the effect of deficiencies in the tunnel crown thickness on pressure tunnels with the posttensioned concrete lining. Based on the lining parameters of the Yellow River Crossing Tunnel, the modeling approach of the posttensioned concrete lining is introduced in detail and a three-dimensional finite element model is established. The three-dimensional finite element model is validated by experimental results from the full-scale model experiment of the Yellow River Crossing Tunnel. Special attention is given to the changes in the deformation, radial displacement, and circumferential stress of the posttensioned concrete lining with gradual decreases in the tunnel crown thickness. The calculation results show that the influence scopes of deficiencies in the tunnel crown thickness are mainly concentrated in the crown and its adjacent parts. The posttensioned concrete lining can still maintain a satisfactory stress state when deficiencies in the tunnel crown thickness exist, and undesirable stress levels may be caused only when the tunnel crown thickness decreases below a certain threshold. Furthermore, cracks are most likely to occur at the external and internal surfaces of the crown and at the internal surface of the crown’s adjacent parts, which is useful for taking measurements regarding the lining tightness and stability.